Exploring Trends in 21st Century Canadian K-12 French as Second Language Research: A Research Synthesis - Arnott, Stephanie; Masson, Mimi; Lapkin, Sharon (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2019)
This research synthesis aims to investigate the broader trends in K-12 French as a second language (FSL) published research from 2000-2017 (inclusive). We assembled a database of 181 peer-reviewed articles relating to FSL education to examine what we already know about specific issues. We used Nvivo 11 (Pro) to facilitate coding the articles for key words and findings (among other codes). Four prevalent research topics emerged in terms of frequency of occurrence: literacy, French language form, French language instruction, and student background. In this article, after exploring each issue by synthesizing main findings, we summarize what we know and what remains to be discovered about each topic. We conclude by suggesting relevant directions for future research, such as focusing on programs other than French immersion and working with First Nations, Métis, and Inuit communities to better understand FSL learning in these contexts.